Development of framework for predictive maintenance in Indian manufacturing sector. (2016) - Srivastava, Nishit Kumar; Mondal, Sandeep
Every machine degrades with time and requires maintenance. Among all types of maintenance policies, predictive maintenance is established as the best form of maintenance policy as numerous benefits are associated with it. Despite all the benefits, it finds restrictive usage in manufacturing companies. A literature survey reveals that limited funds is the major reason for restrictive usage of predictive maintenance, as predictive maintenance is capital intensive. In this paper, a predictive maintenance framework using predictive maintenance models with no investment on technology component is proposed for Indian manufacturing sector.